Comercio informal y su incidencia en el desarrollo económico del país - Gallardo Avendaño, Mayda Jaqueline (2021)
The research carried out entitled "Informal trade and its impact on the economic development of the country", in this research work is presented as informal trade is an important phenomenon today and this is taking more and more place in the economy of the Latin American countries and our country is no exception, the investigative work carried out was motivated by the fact that in our Supreme Law the Constitution of the Republic in its article 329 in its third paragraph, recognizes and guarantees autonomous work, which empowers people develop independent work and work in public spaces where they find it easier without making large payments that do not favor their economy. Regarding the literature review on the subject under investigation, we also find the conceptual framework that includes terms of trade, work, work, self-employment, among others, which are considered the most important when developing the problem, as the doctrinal framework the Review History of Informal Commerce, Informal Commerce in Latin America, Informal Commerce in Ecuador, Description of informal sellers, Classification of informal sellers that are fundamental for the investigation, in the legal framework I develop all the laws regarding the subject. The comparative legislation gives the comparison of Ecuadorian norms with other countries such as Mexico, Argentina, Colombia with respect to informal trade. As for the field research, it allowed me to see how the situation of informal workers in our country is, the contempt they suffer and unworthy work and this as their means of subsisting and surviving every day. The Decentralized Autonomous Governments in their corresponding functions were in charge of regulating and protecting self-employed workers, for which two proposals for reforms to the Organic Code of Territorial Organization, Autonomy and Decentralization and the Organic Law of Popular and Solidarity Economy were presented.